Osteomyelitis treatment in New Zealand white rabbit using impregnated biomaterials with gentamicin– in vivo studies outcome - Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Aziz, Aziah; Ibrahim, Mohd Zulfadzli (2017)
Treatment of osteomyelitis is still a major problem in orthopaedic field. New Zealand White rabbit (NZWR) is acceptable experimental model described to develop effective local delivery of antibiotics osteomyelitis treatment as it can mimics the disease process in human. The objective of this study was to analyze the treatment given via impregnated biomaterials with gentamicin beads in rabbit models. Osteomyelitis was created by inoculation of Staphylococcus aureus ATCC 25923 into the drilled rabbit’s distal femur. Thirty-four (32) NZWR was used during the research. The rabbits were divided into 2 groups; (hydroxyapatite (HA) and calcium sulphate (Ca2SO4)) with four subgroups assessments in (3, 6, 12 and 26) weeks. The response of the treatments against infection was evaluated through gross presentations, radiograph, micro CT, microbiology and histological. The rabbits were sacrificed accordingly to evaluate the healing process of bone. Results showed osteomyelitis changes were noted in all rabbit after inoculation of bacteria at week 3 intervals. Intervention was done after 3 weeks of inoculation. Chronic osteomyelitis was confirmed via radiology and microbial assessments. SPSS was used to evaluate the results. The microbiology analysis revealed there was no bacterium isolated at 26th week interval. In histological interpretation, healing was noted at infected area with appearance of new bone formation at 6 to 26 week of intervals. The micro CT results showed that trebaculae numbers increased significantly (p<0.05) with the treatment. The results show bone healing at 26th week of interval. There was no significant difference between both treatments in the area of radiology, histology and micro CT assessment (p<0.05). The impregnated antibiotics biomaterial showed its function in the treatment of osteomyelitis. In conclusion, these result showed that impregnated biomaterials with gentamicin have roles in treatment of osteomyelitis as added to medical and surgical treatment